2020
DOI: 10.31557/apjcp.2020.21.11.3221
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Molecular Biomarkers in the Diagnosis of Cervical Pre-Cancer and Cancer and Risk Factors in Senegalese

Abstract: Background: Cervical intraepithelial neoplasia (CIN) grading is subjective and affected by substantial rates of discordance among pathologists. Although recent studies have suggested that p16INK4a may be a useful surrogate biomarker of cervical neoplasia, Ki-67 and human papillomavirus testing have also been shown to be useful in detecting neoplasia. The purpose of this study was to determine the expression of p16INK4a and Ki-67 in cervical neoplasia and its correlations with cofactors. Methods: The study invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Positive predictive value =True positives / (True positives + False positives). (Halloush et al, 2008;Diouf et al, 2020;Ghosh et al, 2020). Our study also showed a significant association of Ki-67 and P16 INK4a in the evaluation of true precursor lesion and invasive cancer (χ 2 -value = 91.32* P value is <0.0001).…”
Section: Discussionsupporting
confidence: 70%
“…Positive predictive value =True positives / (True positives + False positives). (Halloush et al, 2008;Diouf et al, 2020;Ghosh et al, 2020). Our study also showed a significant association of Ki-67 and P16 INK4a in the evaluation of true precursor lesion and invasive cancer (χ 2 -value = 91.32* P value is <0.0001).…”
Section: Discussionsupporting
confidence: 70%
“…p16/Ki-67 IHC has been used most frequently throughout the studies. Similar to p16 and Ki-67 IHC alone, an increase in the number of DS-positive biopsy specimens was correlated with a more severe histological diagnosis [ 32 , 41 , 42 , 43 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] and with HPV DNA positivity [ 41 , 42 , 43 , 58 , 59 , 63 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 69%
“…p16/Ki-67 IHC has been used most frequently throughout the studies. Similar to p16 and Ki-67 IHC alone, an increase in the number of DS-positive biopsy specimens was correlated with a more severe histological diagnosis [32,[41][42][43][53][54][55][56][57][58][59][60][61][62][63] and with HPV DNA positivity [41][42][43]58,59,63] (Table 2). Ki-67 was generally expressed in combination with p16 IHC, as DS positivity.…”
Section: Resultsmentioning
confidence: 75%
“…Despite the large number of publications dedicated to various aspects of cervical carcinogenesis, pathologists still play an important role in the development of diagnostic approaches and targeted therapies aimed at tumors characterized by a certain phenotype and the presence of biomarkers that allow the response to targeted therapy to be predicted, enabling the monitoring of response to treatment [92]. It should be emphasized the high importance of modern screening studies in various countries aimed at detecting neoplasms of the cervix using such well-known markers as P16 and Ki-67 [93][94][95][96]. Immunohistochemistry is used to study both the various stages of carcinogenesis, but also to search for effective prognostic and predictive factors.…”
Section: Discussionmentioning
confidence: 99%